Studying the risk spillover effects of the carbon market and high-carbon-emission industries under economic uncertainty - Han, Jiatong; Sun, Qing; Jiang, Yanbo (Frontiers in Environmental Science, 2024)
In this paper, we select the China Carbon Market Price Index, which reflects the overall price changes in China's carbon market (CCM), andWith increasing global warming, global economic growth and sustainable development have been seriously affected, so investigating the spillover effects between the carbon market and high-carbon-emission industries is vital for achieving decrease of emissions and energy conservation. The paper employs the TVP-VAR-BK model to examine the risk spillover effects between the carbon market and high-carbon-emission industries in China from a frequency domain viewpoint. Employing the nonparametric quantile Granger causality test, it delves further into the effects of economic policy uncertainty (EPU) in China on the degree of risk spillovers between the carbon market and high-carbon-emission industries. There are significant risk spillover effects between the carbon market and high-carbon-emission industries. During the short term, the carbon market affects the cement industry more than the electric power and steel industries. However, the carbon market is affected by the volatility of the high-carbon-emission industries over the long term. In addition, the effect of EPU on the magnitude of risk spillovers between the carbon market and high-carbon-emission industries is nonsignificant at extreme quartiles and significant at the middle quartile level, which is typically asymmetric.